Pengaruh IPM, UMK, Pertumbuhan Ekonomi, dan TPAK terhadap Tingkat Pengangguran Terbuka di Jawa Tengah - Amalia, Lathifah; Putri, Rizka; Aprelia, Rizky (Universitas Negeri Surabaya, 2024)
Poverty and unemployment are two main issues that are interrelated in Indonesia's economic development, especially in Central Java Province. This study aims to analyze the effect of the Human Development Index (HDI), Regency/City Minimum Wage (UMK), and GRDP on the Open Unemployment Rate in Central Java Province 2019-2023. The data used includes secondary data obtained from the Central Statistics Agency of Central Java Province. The research method used is a quantitative method with panel data regression analysis. This study uses EViews 12 as a statistical tool in testing the selection of models between FEM, CEM, and REM to testing the hypothesis. The results of this study reveal that the HDI, UMK, and GRDP variables have a significant effect on the Open Unemployment Rate in Central Java Province 2019-2023. Meanwhile, the TPAK variable does not have a significant effect on the Open Unemployment Rate in Central Java Province 2019-223. Meanwhile, the variables of HDI, UMK, PDRB, and TPAK have a significant influence and simultaneously on the Open Unemployment Rate in Central Java Province 2019-2023.